Study on natural vegetation types at Chu River basin, Thanh Hoa province - Tai, Vu Anh; Tu, Nguyen Huu (Academia Journal of Biology, 2012)
Study on vegetation types at a river’s basin will contribute in scientific basic for the prevention of natural calamities such as drought, flood... by the role of vegetation’s water controlling. Within Chu river basin, there were determined 13 types and 4 subtypes of natural vegetation and classified into tropical zone (under 600 m alt.), cool subtropical zone (600-1500 m alt.) and cold subtropical zone (over 1500 m alt.). There were 2 tropical types on limestone as tropical season rainy secondary evergreen forest and scrub. At the same elevation with them were types of the tropical closed season rainy evergreen forest with broad leaves on non-limestone soils; tropical season rainy secondary bamboo forest on non-limestone soils; tropical season rainy secondary scrub on non-limestone soils and tropical season rainy secondary grassland on non-limestone soils. On the cool subtropical zone, the types were: subtropical season rainy secondary bamboo forest on non-limestone soils; subtropical season rainy secondary scrub on non-limestone soils and the subtropical season rainy secondary grassland on non-limestone soils. On the cold subtropical zone, there were 2 types as dwarf forest and the subtropical closed season rainy evergreen forest mixed broad leaves and pines.